2012
DOI: 10.1007/s11356-012-1398-7
|View full text |Cite
|
Sign up to set email alerts
|

Metal content in street dust as a reflection of atmospheric dust emissions from coal power plants, metal smelters, and traffic

Abstract: Resuspended street dust is a source of inhalable particles in urban environments. Despite contaminated street dust being a possible health risk factor for local population, little is known about the contribution of atmospheric dust emissions and other factors to the content of toxic metals in street dust. The impact of smelting, traffic, and power plants on metal contaminates in street dust is the focus of street dust sampling at 46 locations in the Witbank area (Republic of South Africa). This area is charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…For example, the outdoor mean (11700 µg/g) and median (4620 µg/g) dust Mn concentrations from Bagnolo Mella are several-fold higher than mean (2260 µg/g) and median (1440 µg/g) street dust Mn concentrations from Witbank, South Africa, (Zibret et al, 2013) site of an active ferromanganese steel plant (Tables 1 and 3), while the highest outdoor dust Mn levels measured in Bagnolo Mella (~80,000 – 180,000 µg/g) were several fold higher than the highest level reported from Witibank (20,000 µg/g). Notably, that study also reported a significant inverse relationship between dust Mn levels and distance from the steel plant, as we observed in Bagnolo Mella.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the outdoor mean (11700 µg/g) and median (4620 µg/g) dust Mn concentrations from Bagnolo Mella are several-fold higher than mean (2260 µg/g) and median (1440 µg/g) street dust Mn concentrations from Witbank, South Africa, (Zibret et al, 2013) site of an active ferromanganese steel plant (Tables 1 and 3), while the highest outdoor dust Mn levels measured in Bagnolo Mella (~80,000 – 180,000 µg/g) were several fold higher than the highest level reported from Witibank (20,000 µg/g). Notably, that study also reported a significant inverse relationship between dust Mn levels and distance from the steel plant, as we observed in Bagnolo Mella.…”
Section: Discussionmentioning
confidence: 92%
“…The NIPI of the seven metals for each sampling site was defined as follows [33]: (2) ...where PI imax is the maximum PI value of each heavy metal and PI iave is the average PI value of each heavy metal. The NIPI was classified as: non-pollution (NIPI≤0.7), warning line of pollution (0.7<NIPI≤1), low level of pollution (1<NIPI≤2), moderate level of pollution (2<NIPI≤3), and high level of pollution (NIPI>3) [33].…”
Section: Methods Of Heavy Metal Pollution Assessmentmentioning
confidence: 99%
“…Several categories of contaminates, such as heavy metals [1,2] and polycyclic aromatic hydrocarbons (PAHs) [3], etc., are continuously emitted into the terrestrial environment, thus posing a great threat to human health [3][4][5]. Nowadays, more and more people dwell in urban areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coal combustion generates a byproduct, commonly known as coal ash, which consists of small particles that contain polycyclic aromatic hydrocarbons; naturally occurring radioactive materials; and a variety of heavy metals including aluminum, arsenic, iron, lead, mercury, and copper (7)(8)(9)(10)(11)(12)(13). In 2014, the United States alone produced 130 million short tons of coal ash -a marked increase from the previous two years (14).…”
Section: Background Coal Ash and Its Componentsmentioning
confidence: 99%